Correlative 3D-imaging of Pipistrellus penis micromorphology: Validating quantitative microCT images with undecalcified serial ground section histomorphology - Herdina, Anna Nele; Plenk, Hanns; Benda, Petr; Lina, Peter H C; Herzig-Straschil, Barbara; Hilgers, Helge; Metscher, Brian D (Journal of morphology, 2015)
Detailed knowledge of histomorphology is a prerequisite for the understanding of function, variation, and development. In bats, as in other mammals, penis and baculum morphology are important in species discrimination and phylogenetic studies. In this study, nondestructive 3D-microtomographic (microCT, µCT) images of bacula and iodine-stained penes of Pipistrellus pipistrellus were correlated with light microscopic images from undecalcified surface-stained ground sections of three of these penes of P. pipistrellus (1 juvenile). The results were then compared with µCT-images of bacula of P. pygmaeus, P. hanaki, and P. nathusii. The Y-shaped baculum in all studied Pipistrellus species has a proximal base with two club-shaped branches, a long slender shaft, and a forked distal tip. The branches contain a medullary cavity of variable size, which tapers into a central canal of variable length in the proximal baculum shaft. Both are surrounded by a lamellar and a woven bone layer and contain fatty marrow and blood vessels. The distal shaft consists of woven bone only, without a vascular canal. The proximal ends of the branches are connected with the tunica albuginea of the corpora cavernosa via entheses. In the penis shaft, the corpus spongiosum-surrounded urethra lies in a ventral grove of the corpora cavernosa, and continues in the glans under the baculum. The glans penis predominantly comprises an enlarged corpus spongiosum, which surrounds urethra and baculum. In the 12 studied juvenile and subadult P. pipistrellus specimens the proximal branches of the baculum were shorter and without marrow cavity, while shaft and distal tip appeared already fully developed. The present combination with light microscopic images from one species enabled a more reliable interpretation of histomorphological structures in the µCT-images from all four Pipistrellus species.
Keywords: Chiroptera; Vespertilionidae; rentgenová mikrotomografie; mužské pohlaví; X-ray microtomography; penis; bone; Histological Techniques; zvířata; male reproductive organ; fylogeneze; zobrazování trojrozměrné; Penis; iodine staining; Imaging, Three-Dimensional; histologické techniky; Phylogeny; Male; X-Ray Microtomography; Animals